2016
DOI: 10.1121/1.4947046
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and acoustic analysis of sibilant fricatives in preadolescents and adults

Abstract: This study describes the production of sibilant fricatives /s/ and /∫/, comparing Scottish English speaking preadolescent children with adults. The materials were the sequences /əCa/ and /əCi/ produced by 15 adults and 15 children aged between 10 and 12 years old. Quantitative analyses were carried out on both spectral information and on ultrasound imaging data on tongue shape, taken from nine successive time points during the fricative. The two groups of speakers were very similar to each other in the articul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
3
19
0
1
Order By: Relevance
“…LOC a-i , the ratio of the two perpendiculars, confirms this observation, returning higher LOC a-i values for both tokens of /ʃ/ than for the token of /s/ (the values are printed on each panel). This pattern, similar to that reported for older children and adults (Zharkova, 2016), illustrates the fact that the child raises the tongue predorsum in order to produce the required constriction for /ʃ/, as opposed to the production of /s/, where the constriction is formed by the tongue tip at the lower teeth, with no need to raise the predorsum in the context of a following low vowel. While the typically developing child differentiates between /s/ and both tokens of /ʃ/, the child who produces a dental stop for both fricatives has a somewhat higher value of the LOC a-i index for the token of /ʃ/ displayed in the right panel than for /s/, but not for the other token of /ʃ/ (middle panel), whose index value is nearly the same as for /s/ (see the bottom row of Figure 3).…”
Section: Analysis Of Ultrasound Data Recorded Without Head-to-transdusupporting
confidence: 69%
“…LOC a-i , the ratio of the two perpendiculars, confirms this observation, returning higher LOC a-i values for both tokens of /ʃ/ than for the token of /s/ (the values are printed on each panel). This pattern, similar to that reported for older children and adults (Zharkova, 2016), illustrates the fact that the child raises the tongue predorsum in order to produce the required constriction for /ʃ/, as opposed to the production of /s/, where the constriction is formed by the tongue tip at the lower teeth, with no need to raise the predorsum in the context of a following low vowel. While the typically developing child differentiates between /s/ and both tokens of /ʃ/, the child who produces a dental stop for both fricatives has a somewhat higher value of the LOC a-i index for the token of /ʃ/ displayed in the right panel than for /s/, but not for the other token of /ʃ/ (middle panel), whose index value is nearly the same as for /s/ (see the bottom row of Figure 3).…”
Section: Analysis Of Ultrasound Data Recorded Without Head-to-transdusupporting
confidence: 69%
“…In the right panel of Figure 2, curvature degree is a ratio of the line CD (a perpendicular from the point on the tongue curve furthest away from AB, the straight line between two ends of the tongue curve) to the line AB. Curvature degree was preferred in this study to another measure of tongue bunching, the dorsum excursion index, used in some of our previous studies (e.g., Zharkova et al, 2015b;Zharkova, 2016), because the latter measure was shown in Zharkova et al (2015a) to be affected by head-to-transducer stabilisation in the case of /ʃ/, while curvature degree had similar results for /ʃ/ across the 2 stabilisation conditions.…”
Section: Quantitative Indices For Analysing Tongue Shapementioning
confidence: 96%
“…Specifically, the speaker needs to be able to separately control the tip/blade of the tongue, which is making the constriction for the consonant, and the rest of the tongue, which is involved in achieving the raised and advanced position required for the following vowel gesture. In consonant-/i/ syllables, substantial midsagittal tongue shape adjustments have been documented for adults and for pre-adolescent children in fricative consonants, with gradual changes towards the vowel tongue shape (Zharkova, 2016). Particularly, between mid-/s/ and the consonant offset, there was a noticeable change on a measure reflecting progressive raising and advancement of the tongue predorsum towards the high front vowel (cf.…”
Section: Tongue Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The class of SSD termed SE includes children who have histories of feature-limited speech sound distortions, generally on the most challenging manner classes of speech sounds in a language (e.g., fricatives, affricates, liquids), which for some speakers may persist for a lifetime with or without treatment (Boyce, 2015;Flipsen, 2015;Klein, Byun, Davidson, & Grigos, 2013;Preston & Edwards, 2007, 2009Preston, Hull, & Edwards, 2013;Shriberg, Gruber, & Kwiatkowski, 1994;Sjolie, Leece, & Preston, 2016;Van Borsel, Van Rentergem, & Verhaeghe, 2007;Wren, Miller, Peters, Emond, & Roulstone, 2016;Wren, Roulstone, & Miller, 2012;Zharkova, 2016). There is research support for sociodemographic differences between children who have experienced the across-the-board, age-inappropriate deletion and substitution errors that define SD (e.g., differences in sex; Shriberg, 2010) and children whose speech errors include only the feature-limited distortion errors that define SE.…”
Section: Sdcs Level IVmentioning
confidence: 99%